The structure of speed-strength readiness of the qualified athletes, going in for different kinds of sport - Pyanzin, A. I. (The Russian Journal of Physical Education and Sport, 2019)
High sports results achievement in any kind of sport is impossible without following the principle of proportionality in speed-strength abilities demonstration. The problem of the research is conditioned by great number of not systematized information about speed-strength abilities level and development among qualified athletes, going in for different kinds of sport. Materials. The peculiarities of speed-strength readiness revelation among qualified athletes, going in for different kinds of sport. The results analysis was held in 4 groups of respondents. They had the following qualification: from the 1st category to World-class master of sport in powerlifting, kettlebell lifting, basketball, track-and-field. Research methods. Scientific literature analysis and summarizing, mathematical modeling; pedagogical testing; methods of mathematical statistics. Results. The respondents` high jump was estimated without the weight and with different weight (from 11,5 till 110 kg on shoulders). In general 618 measurements were fulfilled. Taking into account the received results we can judge the proportionality in using speed, speed-strength and strength abilities development in terms of physical training process in different kinds of sport. Adequacy control of the equation, calculates height of a high jump with the weight on the basis of the height of a high jump without the weight. It takes into account the athlete`s body weight and the weight. It shows that it reflects the regularity in the height of jump change. It depends on the weight of poundage. Coefficient of correction introduction into the offered equation would help to provide more precise and detailed estimation of speed-strength abilities level within their all range at speed-strength scale. The equation gives an opportunity to calculate individual model values of the jump height in terms of poundage increase. And helps to estimate the proportionality in the level of the athletes` speed-strength abilities components demonstration. Conclusion. The revealed dynamics of the jump height correspondence with the individually normative level helps to reveal not proportionate speed-strength abilities development means use in terms of physical training process in different kinds of sport. It proves insufficient attention to predominantly speed and predominantly strength components development. Keywords: basketball, kettlebell lifting, athletics, powerlifting, speed-strength abilities, proportionality.